Management of Innovation and Product Development Integrating Business and Technological Perspectives - Cantamessa, Marco; Montagna, Francesca (Springer London : Imprint: Springer, 2016)
Presenting an integrated and holistic perspective on innovation management, and product design and development, this monograph offers a unique and original understanding of how these two perspectives are interconnected. This book explores these themes in a scientifically rigorous manner, associating academic findings with examples from business. It provides readers with the conceptual and decision-making tools required to understand and manage the process of innovation at different levels, from the analysis of industry-wide phenomena to the formulation of a strategy, and from the planning of operations to the management of technical choices. Chapters cover innovation as an economic and social phenomenon, the formulation of innovation strategy, the management of product development processes and projects, and the technical design of products and services. Offering an invaluable resource to postgraduate students in economics, business and engineering, this book is also intended for managers and entrepreneurs.